PENGARUH LATIHAN FORWARD RAISE DUMBELL TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA PERMAINAN BULUTANGKIS ATLET PUTRA KLUB PB YUNIOR TUALANG KABUPATEN SIAK - Ria Mariyana; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is still lack of strength of arm and shoulder muscles when making a stroke, as a result a ball (cock) can not pass through the net in the Junior male athlete of PB club Tualang, Siak. Based on these problems, the researcher provided the exercise of Dumbell Raise Forward for 18 x meeting. The research aims to determine whether there is influence between Forward Raise Dumbell exercises through the strength of arm and shoulder muscle of athletes PB club Junior Tualang Siak, hence when making a strike, it might get the maximum result. The model of this research is the treatment trial (Experiment Research), with a population of it was PB club Junior athletes Tualang Siak, the data in this study was the entire population of 6 people. The instruments used in this research was Expanding Dynamometer test that aimed to measure the strength of the arm and shoulder muscles. After that, it was analyzed by the statistic data, to test for normality with lilifors test at significant level α (0.05). The hypothesis proposed there was the effect of exercise Dumbell Raise Forward to the strength of the arm and shoulder muscles. Based on the analysis of statistic data, there was an average of the pre-test which was 16.3 and the average post-test for T20,5, then the data was normal with an increase of 4.2. Based on T test analysis produced Tcount 13,45 and Ttable 1,943, it means Tcount > Ttabel. In conclusion, there is effect of Forward Raise Dumbell Exercise on the arm and shoulder muscle strength at athletes of PB Junior Male Club Tualang, Siak Regency.Keyword : Forward Raise Dumbell, Arm and Shoulder Muscle Strength.